Tailored Bisacylphosphane Oxides for Precise Induction of Oxidative Stress-Mediated Cell Death in Biological Systems - Almahayni, Karim; Bachir Salvador, Jana; Conti, Riccardo; Widera, Anna; Spiekermann, Malte; Wehner, Daniel; Grützmacher, Hansjörg; Möckl, Leonhard (ACS Chemical Biology, 2024)
Precise cell elimination within intricate cellular populations is hampered by issues arising from the multifaceted biological properties of cells and the expansive reactivity of chemical agents. Current chemical platforms are often limited by their complexity, toxicity, and poor physical/chemical properties. Here, we report on the synthesis of a structurally versatile library of chemically tunable bisacylphosphane oxides (BAPOs), which harnesses the spatiotemporal precision of light delivery, thereby establishing a universal strategy for on-demand, precise cellular ablation in vitro and in viv
Keywords: Assays; Cells; Irradiation; Light; Toxicity